Analisis Pengelolaan Berbasis Manajemen Risiko pada Usaha Bibit Ikan Nila di Nagari Paninjauan Kabupaten Agam (Studi Kasus: Usaha Ikan Nila Pak Danil Paninjauan) - Nurul Wafiq Azizah; Andis Febrian (Lembaga Yasin AlSys, 2026)
Although the management of aquaculture businesses, particularly tilapia fingerling businesses, has received attention in a number of studies, studies that specifically discuss risk management-based management in micro-scale businesses at the local level remain limited. This study aims to analyze risk management-based management and the impact of the risks faced in a tilapia fingerling business in Nagari Paninjauan. This study employed a qualitative approach with a case study design, involving three participants consisting of the business owner and two employees selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using interactive qualitative analysis techniques through the stages of data reduction, data display, and conclusion drawing. The results showed that risk management had been carried out through the stages of risk identification, analysis, evaluation, and management, although it had not yet been implemented systematically and in a structured manner. The main risks faced included weather changes, water quality, pest and disease attacks, and market price instability, which had an impact on declining production, financial losses, and business sustainability. These findings contribute to the development of the concept of risk management in the context of micro-scale aquaculture businesses while broadening understanding of experience-based risk management practices in the field. This study concludes that strengthening risk management is an important aspect of maintaining business sustainability, so business actors and the government need to improve risk management capacity through a more systematic approach. The implications of this study include theoretical and practical contributions, while also opening opportunities for further research related to the integration of technology in risk management.